A study on the relationship between exchange rates and stock prices in Malaysia / Suzilawati Mohamad Noor - Mohamad Noor, Suzilawati (2006)
This project paper studies the relationship between exchange rates and stock prices in Malaysia. The analysis is done on the Kuala Lumpur Composite Index towards the Malaysia Ringgit to US Dollar exchange rate. The purpose of this study is to examine the relationship between exchange rates and stock prices over the period 1990 to 2005. This study applies the Simple Linear Regression analysis to identify whether the stock price are significant with the exchange rates. Result of the analysis shows a weak negative relationship between the stock prices of Kuala Lumpur Composite Index for Malaysia Ringgit to US Dollar exchange rate.